THE DEVELOPMENT OF EARTH QUAKE TEACHING MATERIAL FOR JUNIOR HIGH SCHOOL BY FOUR STEP TEACHING MATERIALS DEVELOPMENT METHOD - Hendri, S.; Setiawan, W. (Physics Department, Faculty of Mathematics and Natural Sciences, Semarang State University, 2016)
The aim of this study is to developed a science teaching material for students on junior high school. The theme of this material are the earthquake phenomenon as the main subject are displayed integratedly into various concepts of science knowledge such as earth science, physics, biology and technology. This study is Research and Development study that developing teaching materials by using The Four Step Teaching Materials Development. The four steps on developing a teaching material which are selection, structurisation, characterization, and didactic reduction process. The final product of this steps is hand out wich titled âBelajar Sains Melalui Fenomena Gempa Bumi (Learning Science through the earth quake phenomenon)â. Then, the teaching materials is tested to get information about concepts indentification, eligibility, and studentâs understanding. This study showed that most of the concepts on this teaching material are quite easy with the correct written main ideas above 75% and the students understanding toward this hand out are falls on good category.Â Beside that, this hand out areÂ validated in four aspects, which are content, material presentment, language & grammar, and grafis.The result stated that the hand out is feasible for use in learning.Penelitian ini bertujuan untuk mengembangkan bahan ajar materi ilmu pengetahuan alam bagi siswa Sekolah Menengah Pertama. Bahan ajar ini mengangkat tema fenomena bencana gempa bumi sebagai pokok pembahasan utama yang mengintegrasikanÂ ilmu kebumian, fisika, biologi dan teknologi. Penelitian ini merupakan bagian dari Research and Development, yaitu mengembangkan bahan ajar menggunakan metode Four Step Teaching Materials Development (4STMD). 4STMD memiliki empat tahapan pengembangan bahan ajar, yaitu proses seleksi, proses strukturisasi, proses karakterisasi, dan proses reduksi didaktis. Produk akhir dari pengolahan bahan ajar ini berjudul âBelajar Sains Melalui Fenomena Gempa Bumiâ. Pengujian terhadap bahan ajar dilakukan dengan mengidentifikasi konsep sulit, menilai kelayakan bahan ajar, dan keterpahaman siswa terhadap bahan ajar. Hasil penelitian menunjukkan sebagian besar konsep-konsep materi yang terdapat pada bahan ajar tergolong konsep mudah, dengan persentase penulisan ide pokok benar diatas 75% dan kualifikasi pemahaman siswa terhadap bahan ajar dikategorikan baik. Hasil penilaian kelayakan bahan ajar dinyatakan bahwa bahan ajar ini layak untuk digunakan dalam pembelajaran.